DISCOURSE ANALYSIS OF MORAL VALUES IN LITTLE MOM MOVIE - Ratna Sari Dewi (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
This research discusses about the moral values of the characters in the “Little Mom” movie. The purpose of this research is to identify the types of moral values in the “Little Mom” movie. The research was conducted by applying descriptive qualitative research. The data sources are taken from the entire “Little Mom” movie and the transcript of the “Little Mom” movie which focuses on the use of moral values and types of moral values. The findings of moral value used Linda and Richard Eyre theory this research, in the “Little Mom” movie are; honesty, bravery, peace ability, confidence, self-discipline, pureness, hard work, respect, love and affection, sensitive and unselfishness, friendly, smart, creative, and gratitude. Then, the most dominant type of moral value found in this movie is self-confidence. From this research, the researcher hopes that after reading this research, the reader can understand about moral values.